Effect of Radiotherapy and Chemotherapy on Serum Glycoproteins of Gynecological Cancers - Dasari, Subramanyam; DS, Raju Naidu; Wudyagiri, Rajendra; Valluru, Lokanatha (Asian Journal of Biological and Life Sciences, 2012)
Glycoproteins are end moieties of the carbohydrate chains are biologically important and essential for functions of glycoconjugates and are reported to be altered in cancer patients. The effect of chemotherapy and radiotherapy on cervical, ovarian and endometrial cancers gynecological cancers were evaluated by the estimation of serum glycoprotein levels including total sialic acid, protein bound fucose and hexose. In patients of gynecological cancers, the levels of total sialic acid, protein bound hexose and fucose were significantly higher as compared to the normal subjects. There is a statistical significance (0.000*) between the levels of serum glycoproteins before and after treatment. The mean and standard deviation of the glycoproteins before and after treatment indicates that there is a statistical significance between two therapies (p<0.05) with respect to the total sialic acid, protein bound hexose and fucose and it is also observed that chemotherapy is more effective than radiotherapy in cervical cancer, where as radiotherapy is more effective for ovarian and endometrial cancer. The results demonstrated that chemotherapy shows better response to cervical cancer where as radiotherapy for ovarian and endometrial cancer.